Protocol for a single-centre randomised controlled trial of multimodal periarticular anaesthetic infiltration versus single-agent femoral nerve blockade as analgesia for total knee arthroplasty: Perioperative Analgesia for Knee Arthroplasty (PAKA). Issue 12 (21st December 2015) - Wall, P D H; Sprowson, A P; Parsons, N; Parsons, H; Achten, J; Balasubramanian, S; Costa, M L
Abstract : Introduction: Total knee arthroplasty (TKA) surgery causes postoperative pain. The use of perioperative injections around the knee containing local anaesthetic, opiates and non-steroidal anti-inflammatory drugs has increased in popularity to manage pain. Theoretical advantages include reduced requirements for analgesia and earlier mobilisation. We propose a single-centre randomised controlled trial of multimodal periarticular anaesthetic infiltration versus femoral nerve anaesthetic blockade as analgesia for TKA. The aim is to determine, in patients undergoing TKA, if there is a difference in patient-reported pain scores on the visual analogue scale (VAS) prior to physiotherapy on day 1 postoperatively between treatment groups. Methods and analysis: Patients undergoing a primary unilateral TKA at University Hospitals Coventry and Warwickshire Hospitals will be assessed for eligibility. A total of 264 patients will provide 90% power to detect a difference of 12 mm on the VAS on day 1 postoperatively at the 5% level. The trial will use 1:1 randomisation, stratified by mode of anaesthetic. Primary outcome measure will be the VAS for pain prior to physiotherapy on day 1. Secondary outcome measures include VAS on day 2, total use of opiate analgesia up to 48 h, ordinal pain scores up to 40 min after surgery, independent functional knee physiotherapist assessment on days 1 and 2. Oxford knee Scores (OKS), EuroQol (EQ-5D) and Douleur Neuropathic Pain Scores (DN2) will be recorded at baseline, 6 weeks and 12 months. Adverse events will be recorded up to 12 months. Analysis will investigate differences in VAS on day 1 between the two treatment groups on an intention-to-treat basis. Tests will be two-sided and considered to provide evidence for a significant difference if p values are less than 0.05. Ethics and dissemination: NRES Committee West Midlands, 23 September 2013 (ref: 13/WM/0316). The results will be disseminated via peer-reviewed publications and conference presentations. Trial registration numbers: ISRCTN 60611146 and EUDRACT Number 2013-002439-10 (protocol code number PAKA-33601-AS117013); Pre-results.